Desain Primer PCR Secara In Silico untuk Deteksi Gen NS1 DENV-2 Strain New Guinea C (NGC) sebagai Diagnosis Dini Demam Berdarah Dengue - Putri, Ni Kadek Sri Adnyani Alit; Yowani, Sagung Chandra (Universitas Pahlawan Tuanku Tambusai, 2025)
Dengue Hemorrhagic Fever (DHF) is a serious infectious disease caused by the Dengue virus, with a high morbidity and mortality rate, especially in tropical countries such as Indonesia. One sensitive and specific method for early diagnosis is Polymerase Chain Reaction (PCR), with the Non-Structural gene 1 (NS1) as the ideal molecular target. This study aims to design an in silico PCR primer that is specific to the NS1 gene of Dengue virus serotype 2 (DENV-2) strain New Guinea C (NGC). The design was done using the Primer3Plus software, and the specificity validation was done through Primer-BLAST against the NCBI database. The selected primary pair has a length of 20 bases with a melting temperature (Tm) of 60.0°C, and a GC content of 50.0% and 45.0%, respectively. The primer was able to amplify the NS1 gene segment along 258 bp specifically without exhibiting cross-amplification of the human genome or other DENV serotypes. These results suggest that the designed primer has strong potential to be further developed as a molecular diagnostic tool for early detection of DENV-2 infection.